PENINGKATAN PRESTASI BELAJAR BIOLOGI MATERI SISTEM PENCERNAAN MAKANAN DENGAN METODE MIND MAPPING PADA SISWA KELAS XI-MIA SMA NEGERI 1 MADAT TAHUN PELAJARAN 2018/2019 - Musliani, Musliani; Desriana, Putri (Universitas Islam Negeri Ar-Raniry, 2020)
The purpose of this research is to determine the using of mind mapping method in improving the learning achievement of biology in the food digestion system material in class XI-MIA of Madat senior high school (SMAN 1 Madat). This research is a classroom action research that is conducted in two cycles. The problems in learning can gradually be solved by applying the mind mapping method. The use of mind mapping method can improve student learning achievement in learning biology of the food digestive system in class XI-MIA of Madat Senior High School (SMAN 1 Madat). This is indicated by the increased percentage of student completeness. In the first cycle (I), the percentage of student learning completeness is 19 (65,52%) students and in the second cycle (II), the percentage increases to 26 (89.66%) students. The mind mapping method gives the meaning for the student because every student experiences real learning by themselves and participates directly in learning. The level success of using the mind mapping method in improving the student learning outcomes in studying food digestive system material in class XI-MIA (SMAN 1 Madat) was successful. This is evident from the results of the assessment when learning by using the mind mapping method has increased. The average of every class increases from the first cycle (I) which is only 70.69% and in the second cycle (II) increase to be 86.21% in the student learning completeness. From the learning observation result, the percentage of 70%Â in the first cycle increases to 86% in the second cycle.